4c+2c+4c-3c+2=-9

Simple and best practice solution for 4c+2c+4c-3c+2=-9 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4c+2c+4c-3c+2=-9 equation:



4c+2c+4c-3c+2=-9
We move all terms to the left:
4c+2c+4c-3c+2-(-9)=0
We add all the numbers together, and all the variables
7c+11=0
We move all terms containing c to the left, all other terms to the right
7c=-11
c=-11/7
c=-1+4/7

See similar equations:

| -2(x-2}=8 | | -4.21+2.5m=2.4m-6.19+2.3m | | X-28+1/2x+14+3x-76=180 | | 3x-16+4x-8=69 | | -8q-9=9-2q | | w/2-5=-2,34 | | 2x-21=x+57=180 | | n/3-7,97=-5.97 | | -5(3x+4)=-2(×-3) | | 3(2/3x+7)=3(2x+4 | | -10+10s=9s+3s+10 | | 4y+9y=169 | | 7=d2+5 | | 2y-15/3=18-y/9 | | y=5(-3)-17 | | 18x-7=7x+12= | | 2j-1=2 | | 4(-2x+3)+x=-5x | | 5+4(x+3)=5x-6 | | 535=7+(n-1)•6 | | -8a+7+2a=-65 | | 8x+3/8=2(4x-1) | | -5y/9=-(y-1) | | -1×n+8.5=14.2 | | -3x-3(5x+17)=3 | | 2m-5=7+4m | | 9x8=40 | | 2(3x+4=6x+8 | | 0.5(12x-10)=0.4(10-5x) | | -5x+1=-5x+3 | | 4y−3+2y=7y+2 | | 3x+5=2(2x+4) |

Equations solver categories